(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
This paper proposes an advanced intelligent home automation system to control the main home functions such as heating, ventilation, air conditioning, shading, lighting, security and food’s preparation. The proposed system designed to detect motion or fire and to make decisions independently. Information about motion, heating, and lightning were collected from three nodes using special sensors that micro-controlled through Arduino with WIFI shield and Xbee to be sent to the Smart Phone for manipulation through Java-based Android application. Delta Learning Rule algorithm was used for decisions making as it is able to distinguish whether it is a dangerous situation or not. Furthermore, the proposed system has a property of generating an alert signal and sends it to the police or fire station through GMS messages.